1968
DOI: 10.1029/wr004i006p01289
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Oxygen 18 and Deuterium Concentrations in the Water Balance of Lakes

Abstract: Natural concentrations of stable isotopes of hydrogen and oxygen are used to determine the water balance of lakes situated in a subhumid climate in southwestern Turkey. A salt lake in that region is used as an index to the molecular exchange process between the lake and the atmospheric moisture. Such use of stable isotopes of oxygen and hydrogen in water balance studies appears to yield promising results and indicates that environmental isotopic studies might be a useful tool in limnological studies. (Key word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 16 publications
(6 reference statements)
2
98
0
4
Order By: Relevance
“…This is sometimes termed the equilibrium evaporation slope, which applies to evaporation of local precipitation [see Gat and Bowser, 1991], but is distinguished from nonequilibrium evaporation slopes, which describe evaporation of allochthonous water sources, i.e., waters introduced by long-distance river transport, regional groundwater flow, or artificial diversions. Local evaporation lines (LELs) have been widely reported from field studies of water bodies [e.g., Dinçer, 1968;Zuber, 1983;Gibson, 2002;Gibson et al, 1993Gibson et al, , 2005 and soil water [e.g., Barnes and Allison, 1988;. In general, soil water LELs have been reported as having lower slopes than open water LELs, attributed to vapor transport through the stagnant, diffusiondominated soil matrix.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This is sometimes termed the equilibrium evaporation slope, which applies to evaporation of local precipitation [see Gat and Bowser, 1991], but is distinguished from nonequilibrium evaporation slopes, which describe evaporation of allochthonous water sources, i.e., waters introduced by long-distance river transport, regional groundwater flow, or artificial diversions. Local evaporation lines (LELs) have been widely reported from field studies of water bodies [e.g., Dinçer, 1968;Zuber, 1983;Gibson, 2002;Gibson et al, 1993Gibson et al, , 2005 and soil water [e.g., Barnes and Allison, 1988;. In general, soil water LELs have been reported as having lower slopes than open water LELs, attributed to vapor transport through the stagnant, diffusiondominated soil matrix.…”
Section: Theorymentioning
confidence: 99%
“…[2] Steady state isotope balance models have often been applied to estimate long-term average water balance conditions for lakes [Dinçer, 1968;Gat, 1995]. When these models are applied in climates with a pronounced seasonality in evaporation rates, especially in environments where ice cover is present, they frequently predict slopes that differ greatly from observations.…”
Section: Introductionmentioning
confidence: 99%
“…1985; Krabbenhoft and Webster, 1995] or stable isotopes [Dincer, 1968;Gat, 1970;Krabbenhofi et al, 1990]. Recently, Curtis and Prepas [1993] suggested that dissolved organic carbon may be conservative in saline lakes, raising the possibility that dissolved organic carbon could be used in chemical balance calculations to approximate seepage.…”
Section: Paper Number 97wr02427mentioning
confidence: 99%
“…The applications of these stable isotopes as tracers for lake mass balance calculations [Dincer, 1968;Gat, 1970] have demonstrated that the isotopic composition of evaporating water vapor is the most difficult to estimate among all parameters which must be determined. The uncertainty involved in methods of estimating the isotopic enrichment of evaporation can result in an uncertainty of more than 50% of the calculated evaporation rate [Zimmermann and Ehhalt, 1970].…”
Section: Introductionmentioning
confidence: 99%